Speed control of DC motor using PID controller implementation with visual basic - Nurul Izzati, Pandak Jabo (2008)
The project focused on speed control of DC motor. The main objective is to design and develop GUI software for speed control experiment, where PID controllers’ design approaches has been applied. The controllers have been designed and the system is simulated using MATLAB to analyze their initial performance. The computer is connected to DC Motor via data acquisition card (DAQ Card) and Visual Basic is used to conduct the experiment. Field-testing is implemented to compare the results between the original and modified system with the PID controller. Finally, the performance of the system is analyzed and validation is done in terms of time response, robustness and percentage of error.